The Relationship of Islam and Modern Science - Muhsin; Bahaking Rama; M. Ilham Muchtar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The relationship between Islam and modern science has a long history and significant contributions to the development of science. During the golden age of Islamic civilization, many Muslim scientists successfully developed various disciplines, such as mathematics, astronomy, medicine, and philosophy. These contributions not only had a significant impact on Islamic civilization itself but also on the development of global science. The Middle Ages witnessed the birth of prominent scientists such as Al-Khwarizmi, Ibn Sina, and Al-Razi, whose works remain recognized today. However, over time, significant challenges have emerged in the development of science in the Islamic world, particularly with the advent of secularism and modernity. In this context, the integration of religious knowledge and science has become a crucial issue, with balance being considered vital to the education and development of Muslims. This article examines the development of science in Islam, explains the relationship between religious knowledge and science, and analyzes the challenges faced by Muslims in developing science in the modern era.